How Do Firms Redline Workers? - Yves Zenou (Institute for the Study of Labor (IZA), 2002)
In a city where individuals endogenously choose their residential location, firms determine their spatial efficiency wage and a geographical red line beyond which they do not recruit workers. This is because workers experiencing longer commuting trips provide lower effort levels than those residing closer to jobs. By solving simultaneously for the land and labor market equilibrium, we show that there exists a unique market equilibrium that determines the location of all individuals in the city, the land rent, the efficiency wage, the recruitment area and the unemployment level in the economy. This model is able to provide a new mechanism for the spatial mismatch hypothesis by taking the firm?s viewpoint. Distance to jobs is harmful not because workers have low information about jobs (search) or because commuting costs are too high but because firms do not hire remote workers.
Keywords: R14; J41; 330; spatial mismatch; recruitment area; efficiency wage; distance to jobs; Städtische Standorttheorie; Städtische Arbeitslosigkeit; Personalbeschaffung; Hinterland; Effizienzlohn; Theorie